The book of evidence - Achinstein, Peter (New York : Oxford University Press, 2001)
What is required for something to be evidence for an hypothesis? In this text, Peter Achinstein, introduces here a basic concept of potential evidence which is characterised using a novel epistemic interpretation of probability.
The dean's challenge -- Concepts of evidence, or how the electron got its charge -- Two major prbabilistic theories of evidence -- What's wrong with these probabilistic theories of evidence? -- Objective epistemic probability -- Evidence, high probability, and belief -- The explanatory connection -- Final definitions and realism -- Two paradoxes of evidence : ravens and grue -- Explanation versus prediction : which carries more evidential weight? -- Old-age and new-age holism -- Evidence for molecules : Jean Perrin and molecular reality -- Who really discovered the electron?
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Evidence; Évidence.; 08.35 philosophy of science; PHILOSOPHY -- Epistemology; Evidence; Bewijs (wetenschap); Evidentie; Evidence